Combined Approach to Eptifibatide and Thrombectomy in Acute Ischemic Stroke Because of Large Vessel Occlusion: A Matched-Control Analysis. Issue 5 (2nd February 2022) - Ma, Gaoting; Sun, Xuan; Cheng, Huiran; Burgin, W. Scott; Luo, Weiliang; Jia, Weihua; Liu, Yajie; He, Wenlong; Geng, Xiaokun; Zhu, Liangfu; Chen, Xingyu; Shi, Huaizhang; et al.
Abstract : Background: In patients undergoing mechanical thrombectomy (MT), adjunctive antithrombotic might improve angiographic reperfusion, reduce the risk of distal emboli and reocclusion but possibly expose patients to a higher intracranial hemorrhage risk. This study evaluated the safety and efficacy of combined MT plus eptifibatide for acute ischemic stroke. Methods: This was a propensity-matched analysis of data from 2 prospective trials in Chinese populations: the ANGEL-ACT trial (Endovascular Treatment Key Technique and Emergency Workflow Improvement of Acute Ischemic Stroke) in 111 hospitals between November 2017 and March 2019, and the EPOCH trial (Eptifibatide in Endovascular Treatment of Acute Ischemic Stroke) in 15 hospitals between April 2019 and March 2020. The primary efficacy outcome was good outcome (modified Rankin Scale score 0–2) at 3 months. Secondary efficacy outcomes included the distribution of 3-month modified Rankin Scale scores and poor outcome (modified Rankin Scale score 5–6) and successful recanalization. The safety outcomes included any intracranial hemorrhage, symptomatic intracranial hemorrhage, and 3-month mortality. Mixed-effects logistic regression models were used to account for within-hospital clustering in adjusted analyses. Results: Eighty-one combination arm EPOCH subjects were matched with 81 ANGEL-ACT noneptifibatide patients. Compared with the no eptifibatide group, the eptifibatide group had significantly higher rates of successful recanalization (91.3% versus 81.5%; P =0.043) and 3-month good outcomes (53.1% versus 33.3%; P =0.016). No significant difference was found in the remaining outcome measures between the 2 groups. All outcome measures of propensity score matching were consistent with mixed-effects logistic regression models in the total population. Conclusions: This matched-control study demonstrated that MT combined with eptifibatide did not raise major safety concerns and showed a trend of better efficacy outcomes compared with MT alone. Overall, eptifibatide shows potential as a periprocedural adjunctive antithrombotic therapy when combined with MT. Further randomized controlled trials of MT plus eptifibatide should be prioritized. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03844594 (EPOCH), NCT03370939 (ANGEL-ACT).